Socio-psychological factors influencing decision-making and implementation of IPM methods among Finnish farmers - Malin, Eliisa; Sorvali, Jaana; Kaseva, Janne; Jalli, Marja (Scientific Agricultural Society of Finland, 2025)
The European Union’s Green Deal aims to reduce the use of chemical pesticides, promoting Integrated Pest Management (IPM) as a sustainable alternative. This study is the first to examine Finnish farmers’ perspectives on IPM adoption using a modified Theory of Planned Behaviour (TPB) framework. We included knowledge, moral norms, and well-being as additional factors to the original TPB components: attitude, subjective norms, and perceived behavioural control. Data were collected via an online survey (n=303), and Structural Equation Modelling (SEM) was used to analyse factor relationships. The model explained 72% of the variance in Intention and 49% in Behaviour. Moral norms, subjective norms, and perceived behavioural control explained attitudes towards IPM. Attitude explained intention directly, which in turn explained actual IPM use. Knowledge of IPM emerged as a strong mediator affecting both intention and usage of IPM methods. Based on our study, there is a need for targeted educational initiatives and support systems to facilitate the adoption of IPM while also considering broader socio-psychological factors that shape farmers’ attitudes.
Keywords: integrated pest management; plant protection; agriculture; behavioural sciences; theory of planned behaviour